1994
DOI: 10.1111/j.1365-3059.1994.tb01644.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Thrips obscuratus on infection and contamination of kiwifruit by Botrytis cinerea

Abstract: Infestation of kiwifruit flowers by Thrips obscuratus, and inoculation with Botrytis cinerea, increased the amount of flower infection, external contamination and internal infection of fruit at harvest. Combination of these treatments was synergistic. The mechanisms of this role of T. obscuratus in the epidemiology of B. cinerea and development of stem‐end rot after cool storage are discussed in relation to commercial production, harvesting and handling procedures. Significant reductions in inoculum available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Moreover, a pathogen which is able to spread easily from the initial infection site by producing secondary spores would also be beneficial, whether these are spread by the insects or locally spread by water splash or wind. A classic example is the spread of Botrytis (which produces secondary spores) by thrips obscuratus Crawford (Thysanoptera: Thripidae) to infect kiwifruit (Fermaud et al 1994). Fusarium tumidum produces only a few secondary spores on gorse (Yamoah et al 2008a) and therefore may not be amenable to spread by insects to cause secondary infection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a pathogen which is able to spread easily from the initial infection site by producing secondary spores would also be beneficial, whether these are spread by the insects or locally spread by water splash or wind. A classic example is the spread of Botrytis (which produces secondary spores) by thrips obscuratus Crawford (Thysanoptera: Thripidae) to infect kiwifruit (Fermaud et al 1994). Fusarium tumidum produces only a few secondary spores on gorse (Yamoah et al 2008a) and therefore may not be amenable to spread by insects to cause secondary infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although the model predicts the development of Botrytis bunch rot epidemics based on grape phenology and environmental conditions, the severity of Botrytis bunch rot is influenced by other factors that were not included in the model. These other factors include wounds caused by abiotic factors [ 17 , 19 , 22 , 23 , 35 ] and by the grape moth Lobesia botrana [ 19 , 87 , 88 ], thrips [ 89 ], birds, and powdery mildew ( Erysiphe necator ) [ 35 ]. The severity of Botrytis bunch rot may also be influenced by cultural practices such as excessive nitrogen fertilization or irrigation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…cinerea infection. This site-specific information could include the susceptibility of specific grape varieties [ 48 , 73 , 105 ] and the factors that predispose berries to infection, such as wounds, insect attacks, incidence of other diseases, or cultural practices [ 17 , 19 , 22 , 23 , 35 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 NZFT has also been shown to be a vector of Botrytis and brown rot (Monilinia fructicola) spores in stonefruit 5 and kiwifruit (Actinidia deliciosa). 6 The damage caused to nectarines by NZFT has resulted in the rejection of fruit by export markets and the designation of NZFT as a quarantine pest. 7 Previous thrips phenology studies using non-baited verticalpanel traps showed that the peak in adult NZFT numbers in a peach orchard (Clyde, Central Otago, New Zealand) was in December/January, during fruit ripening.…”
Section: Introductionmentioning
confidence: 99%